2014
DOI: 10.1007/s00439-014-1477-6
|View full text |Cite
|
Sign up to set email alerts
|

Common genetic variation in and near the melanocortin 4 receptor gene (MC4R) is associated with body mass index in American Indian adults and children

Abstract: Six rare functional coding mutations were previously identified in melanocortin 4 receptor (MC4R) in 6,760 American Indians. Individuals heterozygous for one of these mutations become obese while young. We now investigate whether common non-coding variation near MC4R also contributes to obesity. Fifty-six tag single-nucleotide polymorphisms (SNPs) were genotyped in 3,229 full-heritage Pima Indians, and nine of these SNPs which showed evidence for association were genotyped in additional 3,852 mixed-heritage Am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 36 publications
0
20
1
1
Order By: Relevance
“…Moreover, because we did not find any differences in the total body fat content, and we have noted some trends to the lower SAT content in AA genotype men, we can hypothesize that maybe the carriers of this SNP may have a lesser subcutaneous lipid storage capacity, what can be a reason of visceral fat accumulation and it's clinical consequences, such as metabolic syndrome [47], or the higher risk of T2DM, what has been shown for carriers of this SNP in rs1350341 near the MC4R gene [24]. Some of the investigated SNPs are located close to the non-coding regions of DNA, and the potential associations between adiposity-related traits and non-coding variations are discussed [48][49][50]. The non-coding regions are very interesting and intriguing, but molecular mechanisms for these associations have yet to be clarified, with remembering that they can be in strong LD with causal variants of coding genes regions [48,50].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, because we did not find any differences in the total body fat content, and we have noted some trends to the lower SAT content in AA genotype men, we can hypothesize that maybe the carriers of this SNP may have a lesser subcutaneous lipid storage capacity, what can be a reason of visceral fat accumulation and it's clinical consequences, such as metabolic syndrome [47], or the higher risk of T2DM, what has been shown for carriers of this SNP in rs1350341 near the MC4R gene [24]. Some of the investigated SNPs are located close to the non-coding regions of DNA, and the potential associations between adiposity-related traits and non-coding variations are discussed [48][49][50]. The non-coding regions are very interesting and intriguing, but molecular mechanisms for these associations have yet to be clarified, with remembering that they can be in strong LD with causal variants of coding genes regions [48,50].…”
Section: Discussionmentioning
confidence: 99%
“…However, in another study, the overall prevalence of T2D among Native Americans increased 68% from 1994 to 2004 and is about 2 to 3 times that of non-Hispanic whites, reinforcing the concept that diabetes drivers may be somewhat unique when considering Native Americans (273,274). Associations of various genetic factors and traits among Native Americans, particularly in Pima people, are provided in Table 3 (85)(86)(87)(88).…”
Section: Demographics and Biologymentioning
confidence: 99%
“…Central adiposity is the primary causal factor in developing insulin resistance, the hallmark of metabolic syndrome (MetS) (Roberts et al, 2013). Several studies have reported that mutations in a number of genes including leptin (LEP), leptin receptor (LEPR), pro-opiomelanocortin (POMC), fat mass and obesity-associated gene (FTO) and melanocortin-4 receptor (MC4R) are associated with fat accumulation and obesity development (Martínez et al, 2007;Fawcett et al, 2010;Deliard et al, 2013;Muller et al, 2014). Youssef et al (2013) have reported that high energy intake is associated with the Trp 64 Arg polymorphism of ADRB3 gene, leading to significant increase in the risk of obesity.…”
Section: Obesitymentioning
confidence: 99%